Development of a prototype solar-powered autonomous vehicle prototype with object detection and avoidance system using Raspberry-Pi - Ogonye, O. Solomon; Dagwa Ishaya Musa,; Nurudeen Abdulhakeem Hassan,; Okonkwo, Emmanuel; Kulutuye, Precious (Penerbit Universiti Kebangsaan Malaysia, 2024)
In this study, the development of a solar-powered autonomous vehicle prototype with an object detection and avoidance system was implemented and achieved using Raspberry Pi. The advancements in science and technology research have given rise to the robust adoption of smart means of transportation, from steam engines to energy-efficient means such as solar, electric, and hybrid-powered vehicles to ease transportation of people, goods, and services with increased human comfortability. Autonomous vehicles (AVs)offer a degree of self-control in driving in which a normal car requires a driver to execute such tasks e.g., braking, acceleration, and steering. An autonomous vehicle, requires sensors, controllers, algorithms, actuators, computers, and advanced software embedded in various locations on the vehicle to perform effectively. The study attempted to proffer solutions to the menace of human errors in decision-making while driving through the use of advances in scientific technology that have given rise to modern approaches to problem-solving. In Nigeria, almost 50% of road accidents were a result of poor decisions leading to the loss of lives and properties. The vehicle uses ultrasonic sensors and a USB webcam to detect and avoid obstacles on its path with the aid of a Raspberry Pie program that effectively executes decision-making changes to manoeuvre the vehicle away from objects on a free path. The study observed that as motor frequency is increased the speed of the AV increases and thus covers distances faster as compared to when the frequency is reduced. However, the increase in frequency also consumes energy faster. Charging rates were compared between the grid and solar photovoltaic, the grid system recorded faster charging rates when the vehicle was stationary while the solar photovoltaic charged the vehicle at stationary and in motion.